Revisiting Public School/University Partnerships for Formal Leadership Development: A Brief 30-Year Retrospective - David C. Thompson (Educational Considerations, 2016)
Almost exactly 30 years ago, Kansas State University foresaw the power of partnerships with public schools in preparing new generations of formal school leaders.
Keywords: Public School; University Partnerships; Educational Considerations; academies; institutional support; Retrospective; Kansas State University